KEANEKARAGAMAN SATWA DIKAWASAN MANGROVE DI DESA KATIALADA KECAMATAN KWANDANG KABUPATEN GORONTALO UTARA - Alexander Ruruh; Zeinab Nurlena Y. Suma (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The diversity of animals found in an area can indicate how things are in the area. The purpose of this study was to identify the diversity of animals in the mangrove forest in Katialada Village, Kwandang District, North Gorontalo Regency, especially aves and reptiles. This research was carried out in the village of Bolalo in March – May 2024. The data obtained from the results of surveys and interviews were then processed using qualitative methods. The results showed thet there were 8 typ es of animals, espe cially aves and reptiles, namely there were 7 types of aves and one type of reptile. Damage to mangrove forests in the coastal area of Katialada Village is caused by land use changes which result in changes in the area of mangrove forest.